Application of oral fluid to detect Porcine Reproductive and Respiratory Syndrome (PRRS) by using ELISA - Kuiek, Ah Meng (2015)
Porcine Reproductive and Respiratory Syndrome (PRRS) is disease that is highly contagious and of great economic importance in Malaysia. Therefore, reliable and improved diagnostic methods are needed to help disease surveillance. This study evaluates the use of oral fluid samples instead of serum samples to detect PRRS by using IDEXX ELISA test kit. The study involves two pig farms located at Perak and Selangor, Malaysia. 35 animals were used as subjects from each farm. These 35 animals were divided into 7 different categories: gilts, young sows (2nd to 5th parities), old sows (6th parities and above), and weaners (10 weeks old, 15 weeks old, 20 weeks old, and 25 weeks old). Oral fluid and serum samples were collected from these animals individually whereas pen oral fluid samples were collected from weaners only. The oral fluid and serum samples were tested with IDEXX PRRS Oral Fluid Antibody Test Kit and IDEXX PRRS X3 Antibody Test Kit respectively. Statistical analysis shows that there is significant, strong, and positive correlation between samples for Farm A (p=0.0001, r=0.681) and significant, moderate, and positive correlation between samples for Farm B (p=0.0001, r=0.601). In conclusion, other than serum samples, oral fluids can also be used as diagnostic tool for PRRS surveillance in the farm.